Analisis Framing Pan dan Kosicki Terhadap Pemberitaan Bom Bunuh Diri di Astana Anyar: Pada Media Online detik.com dan cnnindonesia.com - Zam Annisa; Hendra Setiawan (Peneliti.net, 2023)
This research is intended to reveal how the media frames news coverage. Framing analysis was carried out on reporting on the suicide bombing case in Astana Anyar, Bandung on both online media, namely Detik.com and CNNIndonesia.com. The method that researchers use is descriptive qualitative. Researchers obtain data naturally through online news found in both media and present data in the form of words and sentences. Presentation of data is classified based on the theory of Zong Dang Pan and Gerald M. Kosicki in which there are several aspects, namely syntactic, script, thematic, and rhetorical structures. A comparison of the ways of framing news carried out by the two online media is also presented. Based on the research results found similarities and differences in the two media. Both online media use a news writing system with an inverted pyramid, namely presenting the core of the news at the beginning of the news. The differences found can be seen in the background information that is presented after the core of the news. The way of mentioning the suicide bombers in the two media was also the difference that was found afterwards.